Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.21203/rs.3.rs-979767/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Top-Down Projections of the Prefrontal Cortex to the Ventral Tegmental Area, Laterodorsal Tegmental Nucleus, and Median Raphe Nucleus

Abstract: Anatomical and functional evidence suggests that the PFC is fairly unique among all cortical regions, as it not only receives input from, but also robustly projects back to mesopontine monoaminergic and cholinergic cell groups. Thus the PFC is in a position to exert a powerful top-down control over several state setting modulatory transmitter systems that are critically involved in the domains of arousal, motivation, reward/aversion, working memory, mood regulation, and stress processing. Regarding this scenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 180 publications
0
1
0
Order By: Relevance
“…The mPFC might modulate impulsive action and RDM by exerting top-down control on subcortical structures (Dalley et al, 2011). Tracer studies (Carr and Sesack, 2000; Murugan et al, 2017; Souza et al, 2021) have shown that the mPFC sends direct projections to subcortical structures such as the dorsal striatum (DST), the nucleus accumbens (NAc), and the ventral tegmental area (VTA), which are critically involved in impulse control (Dalley and Robbins, 2017). For instance, studies in both humans and rodents have linked trait impulsivity (Buckholtz et al, 2010), impulsive action (Bellés et al, 2021; Urueña-Mendez et al, 2023), and RDM (Oswald et al, 2015) to heightened evoked dopamine (DA) release in the striatum.…”
Section: Introductionmentioning
confidence: 99%
“…The mPFC might modulate impulsive action and RDM by exerting top-down control on subcortical structures (Dalley et al, 2011). Tracer studies (Carr and Sesack, 2000; Murugan et al, 2017; Souza et al, 2021) have shown that the mPFC sends direct projections to subcortical structures such as the dorsal striatum (DST), the nucleus accumbens (NAc), and the ventral tegmental area (VTA), which are critically involved in impulse control (Dalley and Robbins, 2017). For instance, studies in both humans and rodents have linked trait impulsivity (Buckholtz et al, 2010), impulsive action (Bellés et al, 2021; Urueña-Mendez et al, 2023), and RDM (Oswald et al, 2015) to heightened evoked dopamine (DA) release in the striatum.…”
Section: Introductionmentioning
confidence: 99%